2021
DOI: 10.1177/11779322211025332
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing Draft Genomes Using Genome Resolved Metagenomics Reveal Arsenic Metabolizing Genes and Secondary Metabolites in Fresh Water Lake in Eastern India

Abstract: Rabindra Sarovar lake is an artificial freshwater lake in the arsenic infested eastern region of India. In this study, using the genome resolved metagenomics approach; we have deciphered the taxonomic diversity as well as the functional insights of the gene pools specific to this region. Initially, a total of 113 Metagenome Assembled Genomes (MAGs) were recovered from the two predominant seasons, that is, rainy (n = 50) and winter (n = 63). After bin refinement and de-replication, 27 MAGs (18 from Winter seaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 104 publications
(163 reference statements)
0
3
0
Order By: Relevance
“…1C ) ( 3 ). Similarly, a recent metagenomic study in freshwater samples detected prochlorosin ORF sequences ( 25 ). Furthermore, in laboratory conditions, the expression of procA reaches its maximum level during the exponential phase of Prochlorococcus MIT9313 ( 10 ).…”
Section: Introductionmentioning
confidence: 88%
“…1C ) ( 3 ). Similarly, a recent metagenomic study in freshwater samples detected prochlorosin ORF sequences ( 25 ). Furthermore, in laboratory conditions, the expression of procA reaches its maximum level during the exponential phase of Prochlorococcus MIT9313 ( 10 ).…”
Section: Introductionmentioning
confidence: 88%
“…The Rabindra Sarovar lake is an artificial freshwater lake were cyanobacterial blooms occur regularly due to anthropogenic pressures which are known to be toxic, especially in freshwater. The presence of arsenic metabolism and MRGs in the retrieved genomes indicates that the microorganisms have adapted to this contamination (Ghosh et al 2021 ) (Table 3 ). Ahmad et al ( 2021 ) reported a metagenomics study from Dal lake an urban freshwater lake, highlighted the functional activities of the microbial populations are altered due to variations in environmental temperature and anthropogenic pressures that were higher in the summer period.…”
Section: Lake Ecosystemmentioning
confidence: 99%
“…In most of the metagenomic studies from lake water systems in India revealed the dominance of Proteobacteria, Bacteroidetes, Chloroflexi Firmicutes, Actinobacteria, Cyanobacteria, Verrucomicrobia, and Planctomycetes (Ahmad et al 2021 ; Ghosh et al 2021 ; Rathur et al 2017; Raina et al 2019 ; Chakraborty et al 2020a ; b; 2021 ). Similar results were reported from different countries lake ecosystems such as Wadi Namar Lake from Riyadh, Saudi Arabia (Alotaibi et al 2022 ), Keenjhar, Rawal and Saif-ul-Muluk lakes in Pakistan (Saleem et al 2019 ), and Lake Meyghan, Iran (Naghoni et al 2017 ).…”
Section: Lake Ecosystemmentioning
confidence: 99%